PENGARUH MODEL PEMBELAJARAN KOOPERATIF STAD BERBANTUAN MIND MAP TERHADAP HASIL BELAJAR IPA DAN SELF EFFICACY SISWA KELAS VIII SMP - Kumala Sari, Ni Putu Indah (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
This study aims to (1) describe the difference of learning outcomes of science and self efficacy of grade VIII junior high school students using cooperative learning model of STAD assisted by mind map and direct learning model, (2) to describe the difference of learning outcomes of science students of grade VIII of junior high school using cooperative learning model STAD assisted by mind map and direct learning model, and (3) to describe the difference of self efficacy of grade VIII SMP students using cooperative learning model of STAD assisted by mind map and direct learning model. The focus of this research problem is the influence of STAD cooperative learning model on student learning outcomes and self efficacy. This type of research is a quasi-experimental non-equivalent pretest-posttest control group design. The population in this study were all students in grade VIII of SMP Negeri 2 Kuta Selatan consisting of 30 students. The research sample was taken based on group random sampling technique. The data in this research are the scores of students science learning outcomes and self efficacy scores analyzed using the Multivariate Analysis of Variance (MANOVA) test. The result of the research shows that (1) there are differences of learning outcomes of science and self efficacy of students using cooperative learning model of STAD assisted by mind map and direct learning model, (2) there is difference of learning result of science student learning with cooperative model of mind map-assistedSTAD and model direct learning, (3) there are differences in self-efficacy of students who learn with the STAD cooperative model and direct learning models.